Improving phosphorus availability in an acid soil using organic amendments produced from agroindustrial wastes - Ch'ng, Huck Ywih; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Hindawi Publishing Corporation, 2014)
In acid soils, soluble inorganic phosphorus is fixed by aluminium and iron. To overcome this problem, acid soils are limed to fix aluminium and iron but this practice is not economical. The practice is also not environmentally friendly. This study was conducted to improve phosphorus availability using organic amendments (biochar and compost produced from chicken litter and pineapple leaves, resp.) to fix aluminium and iron instead of phosphorus. Amending soil with biochar or compost or a mixture of biochar and compost increased total phosphorus, available phosphorus, inorganic phosphorus fractions (soluble inorganic phosphorus, aluminium bound inorganic phosphorus, iron bound inorganic phosphorus, redundant soluble inorganic phosphorus, and calcium bound phosphorus), and organic phosphorus. This was possible because the organic amendments increased soil pH and reduced exchangeable acidity, exchangeable aluminium, and exchangeable iron. The findings suggest that the organic amendments altered soil chemical properties in a way that enhanced the availability of phosphorus in this study. The amendments effectively fixed aluminium and iron instead of phosphorus, thus rendering phosphorus available by keeping the inorganic phosphorus in a bioavailable labile phosphorus pool for a longer period compared with application of Triple Superphosphate without organic amendments.